Prototype Automatic Transfer Switch (ATS) on the Generator to Anticipate Blackouts - Irfani M., Maslahatul; Herlina, Amalia; Safrudin, Safrudin (Universitas Ahmad Dahlan, 2021)
It has been designed and built a device to transfer the load from the PLN to the generator called the Automatic Transfer Switch (ATS) and at the same time able to turn on the generator automatically called Automatic Main Falure (AMF). This tool is in the form of a prototype that has successfully fulfilled its function so that it can be applied for domestic or industrial purposes. This tool is also economically valuable, because the price of its production is able to compete with similar products in the market, but by having more capabilities in the form of fuel detection and lubrication. With the results of the study covering the duration of the network load outages during the process of switching the electricity grid from PLN to the generator on average 3.5 seconds, and 0 seconds (instantaneous) during the process of switching the electricity grid from the generator to PLN, the ATS-AMF that is created automatically is able to light Genset engine when PLN dies and turns off the Genset engine when PLN starts again after it goes out, and the ATS-AMF that is made automatically is able to give a warning (alert) to the engine operator when Gasoline or Oil will run out at the level of 20% of the capacity of Gasoline or Oil.